Foglalkoztatási lehetőségek a határon túl – avagy a migrációs folyamatok vizsgálata a kelet-közép-európai térben (Employment Opportunities beyond the Border – Analysis of Migration Trends in Central-Eastern-European Space) - Katalin Lipták (DETUROPE)
In this study I examine the main factors of migration, in particular to globalization, as well as the unemployment. This factor affects the migration processes. The main effect of globalization on labor market is manifested most in demand for labor flexibility and growth rather than an overall reduction in demand site. The factors of production in the global economy will be higher mobility than before, so the workforce as an economic factor in the globalization movement across national boundaries thereof. The processes associated with adverse global decline in the working age population (whose evolution I demonstrate this with calculating the Hoover index). A variety of factors can not easily be separated from each other of migration trends with respect. An increasing number of skilled workers get work in Eastern Europe.